Assessment of the palatability of Atlantic salmon by NMR spectroscopy - L. S. Abramova; A. V. Kozin; E. S. Guseva; K. A. Lavrikova (Пищевые системы, 2023)
H-NMR spectroscopy was used to study the metabolic profile of Atlantic salmon muscle tissue during heat treatment and storage to assess the taste of products. It has been established that when steaming fish, the amount of compounds such as trimethylamine (TMA), taurine (Tau), glutamic acid (Glu), lysine (Lys), proline (Pro), serine (Ser), γ-aminobutyric acid (GABA), creatinine (Cret) increased in broth compared to raw fish, and Tau and Cret accumulated in cooked fish. The content of TMA, which gives a fishy smell to the product, increased dramatically in cooked fish, regardless of the cooking duration, and at the same time an increase in dimethylamine (DMA) was observed in cooked fish. The processing of the data array of the content of metabolites by the method of principal components was carried out and a clear separation of fish and broth samples was revealed, as well as the difference between fish stored for a long time and the original sample. The taste qualities of fish raw materials before and after heat treatment were evaluated using the taste active value (TAV) of the main compounds characterizing sweet, bitter, sour tastes, as well as umami taste. The values of the taste threshold of compounds, which are widely used for a comprehensive assessment of various food products, were taken for calculations. The TAV for the broth when steaming Atlantic salmon for 30 min was 6.27 ± 0.06, and with an increase in time to 60 min, it decreased to 5.61 ± 0.09. During long-term storage of fish, there was a sharp decrease in the umami taste index and an increase in bitter taste, which is due to hydrolytic processes occurring during product spoilage. It is concluded that the NMR spectroscopy method makes it possible to quantify the change in the main metabolites in Atlantic salmon samples during heat treatment and storage, and TAV calculated from the content of free amino acids, nucleotides and organic acids provides an objective description of the taste of the product.